The costs and benefits of restoring a continent's terrestrial ecosystems. Issue 2 (13th September 2021) - Mappin, Bonnie; Ward, Adrian; Hughes, Lesley; Watson, James E. M.; Cosier, Peter; Possingham, Hugh P.
Abstract: The rise in global commitments to restore habitat underlines its importance to halt biodiversity loss and abate climate change. To effectively plan for landscape‐scale restoration efforts, decision makers need to prioritise where restoration should occur and have a method to estimate its cost. Here, we describe a systematic approach to determine where cost‐effective restoration actions should be located to achieve targeted levels of ecosystem coverage across Australia without compromising agricultural production. We find that spending approximately AU$2 billion (0.1% of Australia's 2019 Gross Domestic Product) annually for 30 years could restore 13 million ha of degraded land without affecting intensive agriculture and urban areas. This initiative would result in almost all (99.8%) of Australia's degraded terrestrial ecosystems reaching 30% vegetation coverage, enabling a trajectory to recover critical ecological functions, abate almost one billion tonnes of carbon dioxide equivalent and produce AU$12–46 billion net present value in carbon offset revenue. The carbon market revenue is estimated to cover up to 111% of the investment required for the restoration. Our research shows that the recovery of degraded ecosystems in Australia is both attainable and affordable. Synthesis and applications . With growing international restoration commitments, governments and environmental organisations need methods to plan and budget their commitments. Here, we present a systematic approach to determine where restoration actions should be located in Australia to achieve targeted vegetation coverage and quantify the expected costs, carbon abatement and revenue. This study is an important advance that will aid governments and environmental organisations by providing financial and spatial planning methods to progress their restoration commitments. Abstract : With growing international restoration commitments, governments and environmental organisations need methods to plan and budget their commitments. Here, we present a systematic approach to determine where restoration actions should be located in Australia to achieve targeted vegetation coverage and quantify the expected costs, carbon abatement and revenue. This study is an important advance that will aid governments and environmental organisations by providing financial and spatial planning methods to progress their restoration commitments.